درجة ممارسة مديري مدارس الموهوبين فى المملكة العربية السعودية لضوابط المنظمة المتعلمة من وجهة نظر المعلمين - اليامى، نوف جارالله بن علي; ابن طريف، عاطف بن عمر صالح (الجمعية الأردنية للعلوم التربوية, 2018)
The study aimed at recognizing the degree of practice of gifted people schools principals in the kingdom of Saudi Arabia to controls of the educated organization from the point of view of teachers. The researcher used the descriptive surveying method. A random stratified sample was selected from (310) male/ female teachers (West, Central, and East) in the Kingdom of Saudi Arabia. To achieve the objective of the study, a questionnaire was constructed consisting of (54) paragraphs divided into five areas. The results of the study showed that the degree of practicing of principals of gifted schools in Saudi Arabia to the controls of the educated organization from the point of view of their teachers was moderate in all fields. Moreover, there was no significant difference in the degree of practicing the controls of the educated organization due to the variables (gender and experience), except for the field of (personal empowerment and mental models) and for the benefit of the experienced (10 years and more).
هدفت الدراسة تعرف درجة ممارسة مديري مدارس الموهوبين في المملكة العربية السعودية لضوابط المنظمة المتعلمة من وجهة نظر المعلمين، واستخدمت الباحثة المنهج الوصفي المسحي، وتم اختيار عينة طبقية عشوائية تكونت من (310) معلماً ومعلمة، (غرب، ووسط، وشرق) المملكة العربية السعودية. ولتحقيق هدف الدراسة تم بناء استبانه مكونة من (54) فقرة موزعة على خمسة مجالات، وأظهرت نتائج الدراسة أن درجة ممارسة مديري مدارس الموهوبين في المملكة العربية السعودية لضوابط المنظمة المتعلمة من وجهة نظر المعلمين جاءت بدرجة متوسطة على الأداة ككل وعلى جميع المجالات، وعدم وجود فروق ذات دلالة إحصائية في درجة ممارستهم لضوابط المنظمة المتعلمة تعزى لمتغير (الجنس، والخبرة)، ما عدا مجال (التمكن الشخصي، والنماذج العقلية) ولصالح ذوي الخبرة (10 سنوات فأكثر).
Keywords: الموهوبين -- المملكة العربية السعودية -- المعلمين